A rapid, point of need open cow test - Mendez, Jacy, author; Dandy, David, advisor; Henry, Chuck, committee member; Bailey, Travis, committee member; Hansen, Thomas, committee member (Colorado State University. Libraries, 2023)
In the dairy industry, maintaining non-pregnant (open) cows is expensive, and may require multiple rounds of artificial insemination (AI) for a cow to become pregnant. There is a need for early pregnancy detection in dairy cows, which allows the use of protocols such as prostaglandin F2-alpha (PGF) and gonadotropin releasing hormone (GnRH) to prepare a cow for another round of breeding via AI, with an emphasis on reduced time between each breeding attempt. The current gold standard method for confirming pregnancy in cows is a rectally-guided ultrasound at day 32 after AI. Interferon-tau (IFNT) is a biomarker that can be detected during days 7-28 of pregnancy in cattle, and is expressed by the cow conceptus. The goal of this work was to develop a cow-side test utilizing IFNT as the biomarker for early cattle pregnancy detection. A lateral flow assay (LFA) was chosen and investigated due to its simplicity and ease of use, but was later adapted to utilize the enzymatic oxidation of 3,3',5,5' – Tetramethylbenzidine to amplify the signal in the test line. C-reactive protein was used to develop protocols for aspects of device development involving nitrocellulose, including antibody striping, blocking, and nitrocellulose selection. These protocols were then utilized as optimization of the lateral flow assay was conducted. The resulting LFA has a limit of detection (LOD) of 10 μg/mL, with an LOD of 100 ng/mL in a half-strip format, with some limitations imposed by false positives. This work provides a novel method of detection for pregnancy in cattle and with further development, has the potential for use by dairy farmers in their respective industry.
Keywords: capillary-driven immunoassay; half-strip assay; lateral flow assay; dairy cows; c-reactive protein (CRP); interferon-tau (IFNT)